Social Entrepreneurship as a Solution to Social Problems in the Digital Age - Dona Zahra Hasibuan; Zuhrinal M Nawawi (Penerbit Jurnal Indonesia, 2023)
Entrepreneurship is a process of working on and creating something new creatively and full of innovation, the goal is to benefit others and have added value. Entrepreneurship is a mental attitude of someone who has creativity, is active, creates the power to make something unique and new and can be useful for many people. Entrepreneurship is a process to develop, identify, realize the vision and mission in life. Various circles have started discussing the concept of social entrepreneurship as an innovative solution in solving social problems, where what is meant by social entrepreneurship itself is about how to apply a practical, innovative and sustainable approach to have a positive impact on society, especially the lower economic class and those who marginalized. Social entrepreneurship usually aims to solve economic or social problems. The purpose of social entrepreneurship is the realization of social change in a better or positive direction and solving social problems for the benefit of society